Successful pregnancy after mucinous cystic neoplasm with invasive carcinoma of the pancreas in a patient with polycystic ovarian syndrome: a case report - Conisha Holloman; S. J. Carlan; Lohini Sundharkrishnan; Angela Guzman; Mario Madruga (Journal of Medical Case Reports, 2017)
Abstract Background The incidence of invasive cancer within a mucinous cystic neoplasm of the pancreas varies between 6 and 36%. Polycystic ovarian syndrome is a disorder characterized by hyperandrogenism and anovulatory infertility. One surgical treatment that can restore endocrine balance and ovulation in polycystic ovarian syndrome is partial ovarian destruction. Successful pregnancies following preconception pancreaticoduodenectomies (Whipple procedures) and chemoradiation to treat pancreatic neoplasms have been reported rarely but none were diagnosed with pre-cancer polycystic ovarian syndrome-associated infertility. Gemcitabine is an antimetabolite drug used for the treatment of pancreatic cancer that can have profound detrimental effects on oogenesis and ovarian function. Whether the ovarian destructive property of gemcitabine could act as a method to restore ovulation potential in polycystic ovarian syndrome is unknown. Case presentation A 40-year-old white American woman with a history of pancreatic cancer treatment with a Whipple procedure and chemoradiation with gemcitabine had a successful pregnancy after years of pre-cancerous anovulatory infertility and polycystic ovarian syndrome. She received no fertility agents and delivered full term via a spontaneous vaginal delivery with no pregnancy complications. Conclusion Gemcitabine treatment for pancreatic cancer may result in resumption of ovulation in women with polycystic ovarian syndrome and these women should be counseled accordingly.